A Rapid In-Clinic Test Detects Acute Leptospirosis in Dogs with High Sensitivity and Specificity. (24th March 2016) - Kodjo, Angeli; Calleja, Christophe; Loenser, Michael; Lin, Dan; Lizer, Joshua
Abstract : A rapid IgM-detection immunochromatographic test (WITNESS® Lepto, Zoetis) has recently become available to identify acute canine leptospirosis at the point of care. Diagnostic sensitivity and specificity of the test were evaluated by comparison with the microscopic agglutination assay (MAT), using a positive cut-off titer of ≥800. Banked serum samples from dogs exhibiting clinical signs and suspected leptospirosis were selected to form three groups based on MAT titer: (1) positive (n = 50 ); (2) borderline (n = 35 ); and (3) negative (n = 50 ). Using an analysis to weight group sizes to reflect French prevalence, the sensitivity and specificity were 98% and 93.5% (88.2% unweighted), respectively. This test rapidly identifies cases of acute canine leptospirosis with high levels of sensitivity and specificity with no interference from previous vaccination.